NGHIÊN CỨU CHẾ TẠO VẬT LIỆU POLYME COMPOZIT TRÊN CƠ SỞ NHỰA NỀN POLYESTE KHÔNG NO VÀ SILICAFUM PHẦN II - CẤU TRÚC VÀ TÍNH CHẤT VẬT LIỆU POLYME COMPOZIT TRÊN NỀN NHỰA POLYESTE KHÔNG NO VÀ SILICAFUM KHI CÓ CHẤT LIÊN KẾT - Đạt, Trịnh Minh; Chương, Bùi; Phúc, Bạch Trọng; Phương Nhung, Nguyễn Thị (Vietnam Journal of Chemistry, 2012)
Effects of coupling agent on the structures and properties of polymer composite materials based on unsaturated polyester resin and silicafume were investigated. The viscosity of the polymer composites had decreased with increasing coupling agent content but it generally had better mechanical properties than those without coupling agent and appeared a maximum in mechanical properties at 4.0 wt% coupling agent content. IR analyze indicated that the coupling agent had reacted with unsaturated polyester resin and silicafume. Fe-SEM and TGA demonstrated more homogeneous dispersion of silicafume in the polymer matrix and accompanied by lower thermal decomposition temperature.